"O Menino Poeta" em diferentes versões: um estudo das edições e de aspectos do circuito da obra de Henriqueta Lisboa - Raquel Cristina Baeta Barbosa (2013)
This research has the aim to analyze five different versions of the book O Menino Poeta (The Poet Boy), by Henriqueta Lisboa, published for the first time in 1943, and to build parts of the communication circuit of the book. The mentioned book is nationally acknowledged for being a transition mark in the context of poetry production directed to children and youth and for presenting light topics referring to childhood, folklore, and nature. Besides, the author is respected for her dedication to writing and for contributing effectively to the art of poetry. The methodology of this research is a documental analysis in a historical perspective. It starts with an analytical description of the editions, published from 1943 to 2008, with the intention to point the main characteristics of each version, as well as to compare the differences among them, seeking to build the possible reading protocols and reader models. To achieve this goal, the analysis focus on paratextual elements, parts of the materiality, and also on the relationship between illustration and written texts. After, a broad look was given to the process of production and divulgation of the book, through surveys on documents present in the Critical Fortune of the writer and in the Acervo de Escritores Mineiros (Collection of Writers from Minas Gerais), such as mails, articles, and book reviews; information from the publisherss websites; and informal conversations with people responsible for a publishing company. Therefore, part of the book circuit was rebuilt. The study can be inserted in a multidisciplinary area of Education, Language, Communication, and History, and was guided by studies of the History of the Book, Reading Sociology, and Childrens and Youth Literature, focused specially on poetry. The comparative study of the editions of five different publishers showed differences due to addition, suppression, disposition of texts, paratexts, insertion of illustration and investment on the materiality of the book, which allowed the elaboration of different reading protocols, different directions by the publishers, as well as the projection of new reader models, that means that the same book was presented in different appearances, ensuring new books. The letters exchanged between Henriqueta Lisboa and Mário de Andrade allowed the reconstruction of the process of production and divulgation of the book by the poetess, which preceded its first publication. The analysis of the Critical Fortune, the personal collection of the poetess, the means of divulgation of the book, the publisherss websites, the awards received by the different editions, and informal conversations with a publisher allowed the construction of parts of the communication circuit of the book and a comprehension of its circulation, from the disclosure of the role of publishers, the divulgation processes, the critiques received from specialized and common readers. The thorough study of the different editions of the same book shows that different materiality produces different destinations and different books, new possibilities of meaning construction, as well as enables the circulation of a poetic text contextualized with the demand of each period, thereby allowing the access by new reader generations and new reading for old readers.